Dividend policy and factors influencing : a study of Malaysian listed corporations / Prof. Madya Dr. Norashikin Ismail, Prof. Dr. Rashidah Abdul Rahman and Prof. Dr. Normah Hj. Omar - Ismail, Norashikin; Abdul Rahman, Rashidah; Hj Omar, Normah (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2011)
The study investigates a sample of 526 publicly listed cornparues on Bursa Malaysia during 2005 - 2008. Our results show that for both measurement of dividend policy, past dividend has a positive and significant association with the policy. The results also show that the past dividend payment variable makes the strongest contribution to the prediction of company's dividend payment when the variance explained by all other variables in the model is controlled for. The result is consistent with one of the renowned dividend behavior i.e smoothing of firm's dividend vis-a-vis earnings and growth. Managerial shareholdings on the other hand have a significant positive association with dividend yield and not dividend per share. Other variables of current earnings, institutional ownership, market to book ratio and free cash flow variables are positively associated with dividend payment and significant at the 1% level, while leverage is negatively associated with dividend payment at the I % level. The results of this study generally support previous survey findings and empirical evidences that the company dividend payment policy is influenced by the pattern of past dividend, current earnings, and their investment opportunities.